2017
DOI: 10.1111/bcp.13268
|View full text |Cite
|
Sign up to set email alerts
|

An anti‐nicotinic cognitive challenge model using mecamylamine in comparison with the anti‐muscarinic cognitive challenge using scopolamine

Abstract: This study demonstrated that mecamylamine causes nicotinic receptor specific temporary decline in cognitive functioning. Compared with the scopolamine model, pharmacodynamic effects were less pronounced at the dose levels tested; however, mecamylamine caused less sedation. The cognitive effects of scopolamine might at least partly be caused by sedation. Whether the mecamylamine model can be used for proof-of-pharmacology of nicotinic acetylcholine receptor agonists remains to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 66 publications
0
23
1
Order By: Relevance
“…In a previous exploratory study, we confirmed that administration of 10 and 20 mg of mecamylamine in healthy subjects led to a temporary, dose‐dependent disturbance of several cognitive functions including fine motor coordination and fluency, short‐ and long‐term memory, attention, and concentration . In this study we further investigated the dose–effect relationship of mecamylamine with a higher dose of 30 mg.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous exploratory study, we confirmed that administration of 10 and 20 mg of mecamylamine in healthy subjects led to a temporary, dose‐dependent disturbance of several cognitive functions including fine motor coordination and fluency, short‐ and long‐term memory, attention, and concentration . In this study we further investigated the dose–effect relationship of mecamylamine with a higher dose of 30 mg.…”
Section: Introductionmentioning
confidence: 99%
“…The protocol described in this paper is part of a larger study described in published literature 29,30 and an in press published paper. The results described below are an example of the results of two computerized battery tests, in 12 healthy young male subjects, in a four-way cross-over design.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Since scopolamine is used as a muscarinic acetylcholine challenge model to induce Alzheimer-like, yet temporary, cognitive effect in healthy subjects 27 , CHDR has developed and validated a pharmacological challenge model with mecamylamine. Mecamylamine is a non-competitive nicotinic acetylcholine receptor antagonist 28 which results in cholinergic dysfunction, i.e., transient cognitive deficits, in healthy young males 29,30 .…”
mentioning
confidence: 99%
See 2 more Smart Citations